2012
DOI: 10.4187/respcare.01302
|View full text |Cite
|
Sign up to set email alerts
|

Oxidative Stress Levels in Exhaled Breath Condensate Associated With COPD and Smoking

Abstract: BACKGROUND: COPD is characterized by chronic air-flow limitation. Smoking is the most important factor in the pathogenesis of COPD. Smoking is associated with increased oxidative stress in the lungs. In this study our aim was to evaluate the differences in the burden of oxidative stress in patients with COPD, smokers, and non-smokers by measuring hydrogen peroxide (H 2 O 2 ), malondialdehyde (MDA), and 8-isoprostane levels in the exhaled breath condensate (EBC) samples. METHODS: Eighty subjects were included i… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
53
1

Year Published

2013
2013
2024
2024

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 47 publications
(55 citation statements)
references
References 28 publications
1
53
1
Order By: Relevance
“…Smokers must have stopped smoking for Ն6 h, [15][16][17][18] and they were asked to fast (no eating or drinking) for Ն10 h before coming to the hospital. 3 Smokers were asked not to participate in strenuous activity for 1 h before the fractional exhaled nitric oxide (F ENO ) measurements and 6MWT.…”
Section: What This Paper Contributes To Our Knowledgementioning
confidence: 99%
See 2 more Smart Citations
“…Smokers must have stopped smoking for Ն6 h, [15][16][17][18] and they were asked to fast (no eating or drinking) for Ն10 h before coming to the hospital. 3 Smokers were asked not to participate in strenuous activity for 1 h before the fractional exhaled nitric oxide (F ENO ) measurements and 6MWT.…”
Section: What This Paper Contributes To Our Knowledgementioning
confidence: 99%
“…9 An Arabic translation, but not validated, version of this questionnaire was applied. The SGRQ, self-administrated at the laboratory on the day of the 6MWT, is an airway disease-specific questionnaire divided into 3 subscales: symptoms, activity, and impacts (8,16, and 26 items, respectively). Scores were calculated using score calculation algorithms.…”
Section: Study Protocol and Collected Datamentioning
confidence: 99%
See 1 more Smart Citation
“…It has been shown that in respiratory diseases several oxidative stress markers are measured in exhaled breath condensate, a technique that is simple and noninvasive. 104,112,113 It has been mentioned that some of the samples e.g. sputum, exhaled breath condensate and biopsies are local and as in measurement of metabolites, blood distributes oxidants and anti-oxidants in the body hence blood samples are useful as this is indicative of the body status in general.…”
Section: Markers Of Oxidative Stress: Laboratory Measurementsmentioning
confidence: 99%
“…The measurement of H 2 O 2 in EBC is a new promising noninvasive technique with no underlying disease and would be valuable in the early diagnosis and monitoring of inflammatory diseases [1][2][3][4][5].…”
mentioning
confidence: 99%